New concepts and outcomes for children with hepatoblastoma based on the experience of a tertiary center over the last 21 years (Clinics, 2015)
OBJECTIVE: The aim of this study was to summarize the experience of a tertiary center in treating hepatoblastoma for the last 21 years. PATIENTS AND METHODS: Fifty-eight cases were included. The tumor extent and prognosis were assessed using the PRETEXT system. The following data were analyzed: age at diagnosis, comorbidities, prematurity, treatment modalities, histopathological findings, surgical details and complications, treatment outcomes, chemotherapy schedules, side effects and complications. Treatment outcomes included the occurrence of local or distant recurrence, the duration of survival and the cause of death. The investigation methods were ultrasonography, CT scan, serum alpha-fetoprotein level measurement and needle biopsy. Chemotherapy was then planned, and the resectability of the tumor was reevaluated via another CT scan. RESULTS: The mean numbers of neoadjuvant cycles and postoperative cycles of chemotherapy were 6±2 and 1.5±1.7, respectively. All children except one were submitted for surgical resection, including 50 partial liver resections and 7 liver transplantations. Statistical comparisons demonstrated that long-term survival was associated with the absence of metastasis (p=0.04) and the type of surgery (resection resulted in a better outcome than transplantation) (p=0.009). No associations were found between vascular invasion, incomplete resection, histological subtype, multicentricity and survival. The overall 5-year survival rate of the operated cases was 87.7%. CONCLUSION: In conclusion, the experience of a Brazilian tertiary center in the management of hepatoblastoma in children demonstrates that long survival is associated with the absence of metastasis and the type of surgery. A multidisciplinary treatment involving chemotherapy, surgical resection and liver transplantation (including transplantations using tissue from living donors) led to good outcomes and survival indexes.